Sex differences in Drosophila intestinal metabolism contribute to sexually dimorphic infection outcome and alter gut pathogen virulence - Marko Rubinić; Yi Yu; Aranzazu Arias-Rojas; Kaisy A. Martinez; Wioletta Klimek; Dagmar Frahm; Volker Brinkmann; Nicole Paczia; Kathirvel Alagesan; David Duneau; Igor Iatsenko (Proceedings of the National Academy of Sciences, 2026)
Sexual dimorphism in infection outcomes is widespread, yet its underlying mechanisms remain incompletely understood. Utilizing Pseudomonas entomophila intestinal infection in Drosophila, we demonstrate that sex differences in intestinal redox processes contribute to female-biased susceptibility to infection. Female inability to overcome pathogen-induced oxidative stress results in defecation blockage, pathogen persistence, and host death. Male flies exhibit increased carbohydrate metabolism and pentose phosphate pathway activity—a key antioxidant defense system. This allows males to withstand oxidative stress-induced defecation blockage and clear the pathogen from the intestine, resulting in survival. Notably, we uncovered that Duox-dependent processes contribute to pathology independently of total ROS levels. In parallel, P. entomophila showed increased expression of several virulence factors, including RNA-binding protein Hfq, in the female gut, contributing to female-biased virulence of P. entomophila . Thus, the effect of the gut metabolic environment on host defenses and pathogen virulence determines the sex differences in intestinal infection outcomes.